Pengelolaan Konflik Aktivitas Bisnis Perspektif Islam Pada Manajemen Pasar Induk Puspa Agro Jawa Timur - Citra Rahayu Indraswari; Muhammad Nafik HR (Universitas Airlangga, 2014)
Conflict is something that can not be separated in the process of management of the company. Conflict that managed well will be able to make a positive contribution to the business activities and the achievement of corporate goals. This study used a qualitative research methodology with a case study approach. The selection of a qualitative methodology based on the problem formulation used in this studyThe results of this study indicate that the conflicts that happened in management Central Market Puspa Agro caused by internal and external factor. Internal factor is derived from obscurity powers, functions and roles, monitoring and evaluation weakness, slowness of responds to the problems, the competence of individual differences, the target and task interdependence. External factors consist of the presence of government policies and industry demands. The effect of conflicts are functional and dysfunctional. Conflicts levels are low, optimal and high.Conflict management is applied by stimulation, reduction of conflict and conflict resolution methods. Conflict stimulation methods include the application of the system of reward and punishment and the different treatment of habit . Conflict reduction methods include the provision of a forum for dialogue, joint activities and creating new challenges. Conflict resolution methods include the expansion of resources, compromise, change the variable structure of the company, avoiding and otorative command. REFERENCESAamodt, M.G. 2007. Industrial/Organizational Psychology, An Applied Approach. 5th Edition. United States: Thomson Wordsmoth.Afifuddin, Beni dan Ahmad Saebani. 2009. Metodologi Penelitian Kualitatif. Bandung: Pustaka Jaya.Al Tabari,Ibnu Jasin. 1997. Jami’ Al-Bayan fi Ta’wil Al Qur’an. Vol.9. Saudi: Al Maktabah Al Shamilah.Anoraga, Pandji dan Sri Suyuti. 1997. Perilaku Keorganisasian. Jakarta : PT. Dunia Pustaka Jaya.Avruch. 1991. Introduction: Culture and Conflict Resolution. Dalam: Conflict Resolution: Cross-Cultural Perspective. New York: Greenwood Press.Daft, Richard L. 2011. Understanding Management. 8th Edition. Canada: Cangage Learning.Depag RI. 1989. Al-Qur'an dan Terjemahnya. Surabaya: Surya Cipta Aksara.Ebert dan Griffin. 2005. Business Essentials. New Jersey: Prentice Hall International.Faisal, Sanapiah. 1982. Metodologi Penelitian Pendidikan. Surabaya: Usaha Nasional.Gitosudarmo, Indriyo dan Sudita. 2008. Perilaku Keorganisasian. Edisi Pertama. Jogjakarta: Erlangga.Hafidhuddin, Didin dan Tanjung. 2003. Manajemen Syariah dalam Praktek. Jakarta: Gema Insani Press.Handoko, T. Hani. 1995. Manajemen. Ed.2. Yogyakarta: BPFE Yogyakarta.Kusnadi. 2003. Masalah, Kerjasama, Konflik dan Kinerja. Malang: Tanada.Lewicki,RJ dan J.A.Literer. 1985. Negotiation. Illinois: Homewood.Martoyo, Susilo. 1994. Manajemen Sumber Daya Manusia Edisi Ketiga. Yogyakarta: BPFE Yogyakarta.Marwansyah. 2010. Manajemen Sumber Daya Manusia (Edisi 2). Bandung: Alfabeta.Moleong, M.A. Lexy J. 2011. Metode Penelitian Kualitatif. Bandung: Remaja Rosdakarya.Munawir, A.W. 1997. Kamus Al Munawir Arab-Indonesia Terlengkap. Surabaya: Pustaka Progresif.Nimran, Umar. 1997. Perilaku Organisasi. Surabaya: Citra Media.Qurtubi. 2004. Al Jami’ Al Ahkam Al Qur’an. Vol.5. Saudi: Al Maktabah Al Shawilah.Rivai, Veitzhal. 2005. Manajemen Sumber Daya Manusia Untuk Perusahaan. Jakarta: Raja Grafindo Perkasa.Robbins, Stephen P. 2006. Organizational Behavior: Concepts, Controversies, Applications (7th Ed). New Jersey: Prentice Hall International................................... 1996. Organizational Behavior. New Jersey: Prentice Hall International................................... 1991. Organizational Behavior. New Jersey: Prentice Hall International............................................. Managing Organizational Conflict: A Nontraditional Approach. New York: Prentice Hall.Robbins, Stephen P., Judge. 2006. Organizational Behavior. 12th Edition. New York: prentice Hall.Shiddieqy, Hasbi Ash., Muhammad. 2000. Tafsir Al Qur’anul Majid An Nuur. Cetakan kedua-Ed.2. Semarang: Pustaka Rizki.Shihab, M.Quraish. 004. Tafsir Al Misbah. Cetakan kedua-Vol.13. Jakarta: Lentara Hati.Siswanto, Bedjo. 1990. Manajemen Modern : Konsep dan Aplikasi. Bandung: Sinar Baru.Slide profile PT. Jatim Grha Utama. 2013. Surabaya.Stoner, James A.F., Freeman. 1989. Principle of Management. 4th Edition. England: Longman Higher Education.Suriasumantri, JujunS. 2001. Filsafat Ilmu: Sebuah Pengantar Populer. Jakarta: Pustaka Sinar Harapan.Surwandono dan Ahmadi. 2011. Resolusi Konflik di Dunia Islam. Yogyakarta: Graha Ilmu.Wahyudi. 2008. Manajemen Konflik dalam Organisasi. Bandung: Alfabeta.Wijono, Sutarto. 1994. Konflik dalam Organisasi/Industri dengan Strategi Pendekatan Psikologis. Semarang: Satyawaca.Winardi. 1994. Manajemen Konflik (Konflik Perubahan dan Pengembangan). Bandung: CV. Mandar Maju.Wirawan. 2009. Evaluasi Kinerja Sumber Daya Manusia. Jakarta: Erlangga.Wood, Jack dkk. 1998. Organizational Behavior An Asia-Pasific Perspektve. Queesnland : Bracken Ridge.Yin, Robert K. 2009. Studi Kasus (Desain dan Metode). Jakarta: PT. Raja Grafindo Persada.